THE DOCUMENTATION OF CLEFT LIP AND PALATE PATIENTS AT THE DEWI SARTIKA HOSPITAL IN KENDARI - Subarno, Saktrio Darmono; Ibnu Ikhsan, M. Idris (Jurnal Plastik Rekonstruksi, 2023)
Introduction : Cleft in the lips and palate is a congenital abnormality in the lip and palate. The incidence of oral cleft in the United States is estimated to be 1 in 700 births. Meanwhile, for Indonesia, especially the Southeast Sulawesi region, it has not been well documented. Method : This is a retrospective study to determine the prevalence of cleft lip and cleft palate or labiopalatosc at Dewi Sartika Hospital in Kendari, Southeast Sulawesi between January and December 2018. Result : Prevalence of Labioschisis, Palatoschisis and Labiopalatochisis on January-December 2018 is 23 patients (33%), 13 patients (19%) and 34 patients (49%). Presentation for each of kind unilateral are : unilateral labioschisis is 38 patients (66,7%) and bilateral labioschisis is 19 patients (33,3%). Presentation according to the place of defect labioschisis : right is 10 patients (17,6%), left 28 patients (49,1%), bilateral 19 patients (33,3%). Distribution kind of palatoschizis : complete palatoschizis is 49 patients (89%) and Incomplete palatoschizis is 6 patients (11%). Presentation labioschizis according to sex : Male 40 patients (57%), and female is 30 patients (43%). Conclusion: The prevalence of cleft lip and palate has many forms, kind of labioschisis that large is unilateral labioschisis and localization defect is often on left edge. Complete labioschizis is large than incomplete palatoschizis. Labioschisis is happen more to male.